How the Royal Bhutan police respond to theft cases and how the response impacts the victims ([Thimphu] : [Royal Thimphu College], 2017)
Spiral-bound xerographic copy.
Student research project for BA, Political Science (Capstone Project):(2017).
Includes bibliographical references.
Keywords: Citizen crime reporting -- Bhutan; Police -- Response time -- Bhutan; Police-community relations -- Bhutan; Capstone Project; Police --Bhutan.